The low fee entry strategy and first mover advantage in the ETF market - Mina Glambosky; Kimberly Gleason; Chun Lee; Maryna Murdock (Investment Management & Financial Innovations, 2019)
Academic literature struggles to explain investors’ attitude towards fees and expenses charged by mutual funds. In general, investors have been found to exhibit a puzzling lack of interest in this non-trivial component of their total return, raising questions of rationality of real-world investor behavior. An emergence of exchange-traded funds (ETFs), their rapid proliferation in the past decades and distinct features, such as more simple expense structure, present a valuable opportunity to contribute to the debate surrounding the pricing of funds. To better understand the expense policy/fund flows dynamics, the authors first test a conjecture that later entrants in the ETF markets face a disadvantage in competition for fund flows. Then, they test whether competitive pressure can be successfully overcome by lowering expenses charged to ETF investors. The results suggest that, though it is not necessary to be a first entrant in a fund category to enjoy competitive advantage, an earlier market entry is beneficial for attracting fund flows. It is also found that later entrants’ to the ETF market successfully use the strategy of reducing their expense ratios. Firms with lower net expense ratios obtain greater investment, as evidenced by greater capitalization and market share, supporting our intuition that investors may acknowledge the merits of low-cost ETFs.